In the days of General Emilio Aguinaldo : a study of the life and times of a great military leader, statesman, and patriot who founded the first republic in Asia - Alip, Eufronio M. (Manila : Alip & Sons, Inc., 1969)
There are many short paths to fame, but there is only one lifelong road to true greatness.
Conquest by cross and sword -- Political awakening -- The Aguinaldo family -- Aguinaldo's birth, childhood and schooling -- The Cavite mutiny -- Filipino propagandists -- Aguinaldo enters public life -- Reforms instituted -- Aguinaldo : Mayor by day, Katipunan by night -- Revolution begins -- Aguinaldo begins revolution in Cavite -- Rizal's martyrdom -- The Bonifacio-Aguinaldo episode -- The Biaknabato government -- The Biaknabato pact -- Aguinaldo and other leaders are exiled to Hong Kong -- The Spanish-American war -- Aguinaldo renews war vs. Spain -- Philippine independence proclaimed -- Success of revolutionists -- Manila surrenders -- The Malolos congress -- Philippine republic proclaimed -- The Malolos constitution -- Appraisal of Spanish rule -- The Treaty of Paris -- Filipino American war begins -- Luna's tragic death -- Aguinaldo's capture -- Del Pilar's death at Tirad Pass -- The Schurman and Taft commissions -- Filipino heroes deported -- War statistics -- American pacification measures -- Local government -- The Judiciary -- The Civil regime -- The Federal party -- Other political parties -- Aguinaldo's passive role after war -- Aguinaldo opposes Quezon -- Aguinaldo during World War II -- Japanese occupation of Manila -- The Executive commission -- The Fall of Bataan and Corregidor -- The Japanese-sponsored Philippine republic -- The Allied counter offensive -- The Liberation of the Philippines -- Japan surrenders -- The Return of the Commonwealth -- The Philippine republic is reborn -- Aguinaldo marches on parade -- Problems of the New Republic -- R. P.-U.S. Relations -- Relation with other countries -- The Philippine Presidents from Roxas to Macapagal -- Events under each president -- Change of independence celebration from July 4 to June 12 -- Women in Aguinaldo's life -- The Death of Aguinaldo -- The Diplomacy of the Aguinaldo government -- During the revolution -- The HongKong Junta -- During the Filipino-American war -- Agoncillo in Washington --Agoncillo in Paris -- Aguinaldo's proposals in Washington after the Paris treaty -- Aguinaldo's pace in history
Includes bibliographical references and index.
Keywords: AGUINALDO, EMILIO, 1869-1964; PHILIPPINES -- HISTORY -- 1898-